An integrated simulation approach to the development of assembly system components - Paryanto, Paryanto; Merhof, Jochen; Brossog, Matthias; Fischer, Christian (WGP Congress 2013 - Progress in Production Engineering, 2013)
Commonly, a modelling and simulation approach is used for parameter optimization and system behavior analysis of assembly system components. However, such simulation approaches are often not well integrated or its analysis is still based on a specific physical domain. This paper proposes an integrated simulation approach that can be used for designing, analyzing and optimizing the entire physical domain as well as the control system of mechatronic components in an assembly system. The state-of-the-art, requirements, our concept and the limitations of an integrated simulation approach are explained in this paper. A case study of the development of conveyor systems using the multi-domain simulation tool OpenModelica is also presented. On-going research shows that the integrated approach offers various benefits such as reduced development time and minimized errors, as well as maintenance during the commissioning process.
Keywords: Mechatronics; Modelling; Simulation

Cutting-edge engineering - An innovative approach to better support the engineering and the life cycle of automated production systems - Merhof, Jochen; Franke, Jörg (Advanced Materials Research, 2013)
This article describes how a future engineering of production systems could look like and what the benefits would be. The presented concept is requirement-based and uses a role-concept and aggregation to deal with the increasing complexity of mechatronic systems. The aim is to counteract the increasing complexity of the systems. For this purpose, strategies must be identified and implemented to achieve this. Finally, an approach for implementing this concept is described. © (2013) Trans Tech Publications, Switzerland.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Data model; Engineering; Semantic description of automated production systems

Dreidimensionale Planung, Simulation und Überwachung von Produktionssystemen mit VRML - Feldmann, Klaus; Brossog, Matthias; Merhof, Jochen; Michl, Markus (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2008)
Der Einsatz frei zugänglicher und kostenloser Technologien für die Entwicklung von rechnergestützten Werkzeugen zur Unterstützung von Planern, Herstellern und Betreibern von Produktionsanlagen bietet ein großes Potential zur Effizienzsteigerung vor und während des Anlagenbetriebs. Der vorliegende Artikel zeigt mehrere Ansatzpunkte für den gewinnbringenden Einsatz der VRML-Technologie am Lehrstuhl FAPS der Universität Erlangen auf. Angefangen bei der webbasierten Layoutplanung bietet diese Möglichkeit der 3D-Beschreibung ebenso Möglichkeiten für die Umsetzung einer webbasierten Simulation sowie für unterschiedliche Anwendungen zur Zustandsüberwachung im Rahmen eines Diagnosesystems oder für Entwicklungen im Bereich der betriebsbegleitenden Simulation.
Keywords: Planung; Webtechnologien; VRML

Durchführung von Experimenten und statistische Auswertung - Ramer, Christina; Merhof, Jochen (Handbuch Fügen, Handhaben, Montieren, 2014)
Keywords: Experimente; Simulation

Energy consumption and dynamic behavior analysis of a six-axis industrial robot in an assembly system - Paryanto, Paryanto; Brossog, Matthias; Kohl, Johannes; Merhof, Jochen; Spreng, Simon; Franke, Jörg (Procedia CIRP 23, 2014)
This paper presents an experimental study to validate a dynamic model of a six-axis industrial robot as part of an assembly system and to analyze its power consumption as well as its dynamic behavior. Furthermore, the effect of robot operating parameters (i.e., payload and speed) on the power consumption and the dynamic behavior are analyzed. The investigation shows that the comparative study between simulation and experimental results can be used to improve the model's accuracy and prove that the simulation model represents the real system. Both simulation and experimental results show that the robot operating parameters strongly influence the industrial robot's power consumption and dynamic behavio
Keywords: Energy simulation; Industrial Robot; Systems Engineering

Intuitive Interaction with Virtual Commissioning of Production Systems for Design Validation - Metzner, Maximilian; Krieg, Lorenz; Merhof, Jochen; Ködel, Tobias; Franke, Jörg (Procedia CIRP, 2019)
As industrial production system complexity increases, digital planning and virtual commissioning become critical steps in the design validation phase of automated production systems. Virtual commissioning is used to test system behavior and control logic based on a simulation model. In this paper, we introduce a concept for facilitating non-expert interaction with such systems to further extend the applicability of virtual commissioning to the sectors of employee or customer training, hybrid system analysis and safety validation. A stereographic camera system is used to track the hands of the operator and implement them into a physics-integrated simulation environment. Hence, the operator is able to manually interact with the running virtual system at real time. The implemented system is evaluated for intuitiveness compared to a classical mouse and keyboard setup. The results show potential for the system to facilitate the non-expert interaction with advanced simulation environments.<br
Keywords: Design validation; Simulation; Mechatronics Design

Mechatronic Behavior Analysis of a Customized Manufacturing Cell - Paryanto, Paryanto; Brossog, Matthias; Merhof, Jochen; Franke, Jörg (Proceedings of the 7th World Conference on Mass Customization, Personalization, and Co-Creation (MCPC 2014), Aalborg, Denmark, February 4th - 7th, 2014, 2014)
Analyzing the mechatronic behavior of a manufacturing cell used in a customized manufacturing process is a difficult task with numerous obstacles. Therefore, a method that can be easily used for developing and optimizing a customized manufacturing cell, i.e., universal contacting module (UCM) cell, for the in-circuit testing of electronic modules is desired. In this paper, we present a convenient method using multi-domain simulation tools for analyzing the mechatronic behavior of the UCM cell. The UCM cell, which consists of mechatronic components such as a six-axis industrial robot and conveyor systems, were successfully modeled, simulated, and validated under several payloads. This work also presents a modeling procedure that can be applied by system engineers with a basic background in control systems for analyzing the mechatronic behavior of manufacturing cell components.
Keywords: Multi-Domain Simulation; mechatronic behavior; manufacturing

Prozessflexible Steuerung von Industrierobotern - Brossog, Matthias; Hartmann, Christian; Kohl, Johannes; Merhof, Jochen; Reichenbach, Marc; Fey, Dietmar; Franke, Jörg (wt Werkstattstechnik - Online, 2014)
In addition to individuality and flexibility, the PCB (Printed Circuit Boards) technology is increasingly expected to demonstrate its potential for energy efficiency. This article describes a test system with an industrial robot for the handling of electronic boards including an automatic calibration system based on optical sensors and different measurement concepts for visualization and optimization of energy consumption. The sensors were integrated into the control of the overall testing system by means of OPC UA.
UnivIS-Import:2015-03-09:Pub.2014.tech.IMMD.IMMD3.prozes
Keywords: Steuerung; Energieeffizienz; Sensorik